FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN ON ASSET (ROA) PADA KOPERASI MEGA, KECAMATAN KEDIRI, KABUPATEN TABANAN - Ni Putu Sudarsani; I Made Hary Kusmawan; I Wayan Terimajaya (Universitas Mahendradatta, 2023)
The purposes of this study are 1) To analyze the effect of Non PerformingLoans (NPL) on Return On Assets (ROA) in the Mega Cooperative, Kediri District,Tabanan Regency. 2) To analyze the effect of Capital Adequacy Ratio (CAR) on ReturnOn Assets (ROA) in the Mega Cooperative, Kediri District, Tabanan Regency. 3) Toanalyze the effect of Loan to Deposit Ratio (LDR) on Return On Assets (ROA) in the Mega Cooperative, Kediri District, Tabanan Regency. 4) To analyze the effect ofOperational Cost per Operational Income (BOPO) Return On Assets (ROA) on the MegaCooperative, Kediri District, Tabanan Regency. Multiple linear regression analysis was used to test the effect of NonPerforming Loans (NPL), Capital Adequency Ratio (CAR), Loan to Deposit Ratio(LDR), Operational Income Operating Costs (BOPO) on Return on Assets (ROA) inMultipurpose Savings and Loan Cooperatives . In this study, the defensive variables wereNPL (X1), CAR (X2), LDR (X3), BOPO (X4) while the independent variable was ROA(Y) The research results show 1) The value of the regression coefficient for NonPerforming Loans (NPL) is -0.007, the value of this regression coefficient is negativewhich indicates that there is no unidirectional relationship between the variable NonPerforming Loans (NPL) and Return On Assets (ROA). 2) The value of the regressioncoefficient for Capital Adequacy Ratio (CAR) is -0.013, the value of this regressioncoefficient is negative which indicates that there is no unidirectional relationship betweenthe Capital Adequacy Ratio (CAR) variable and Return On Assets (ROA). 3) The valueof the regression coefficient Loan to Deposit Ratio (LDR) is -0.005, the value of thisregression coefficient is negative which indicates there is no unidirectional relationshipbetween the Loan to Deposit Ratio (LDR) variable and Return On Assets (ROA). 4) Themagnitude of the regression coefficient value of Operational Income Operating Expenses(BOPO) is -0.017, the value of this regression coefficient is negative which indicatesthere is no unidirectional relationship between the variable Operating Income OperatingExpenses (BOPO) to Return On Assets (ROA).